Frequency and risk factors for donor reactions in an anonymous blood donor survey. Issue 9 (11th December 2012) - Goldman, Mindy; Osmond, Lori; Yi, Qi‐Long; Cameron‐Choi, Keltie; O'Brien, Sheila F.
<x xml:space="preserve">Abstract</x> Background Adverse donor reactions can result in injury and decrease the likelihood of donor return. Reaction reports captured in the blood center's database provide an incomplete picture of reaction rates and risk factors. Study Design and Methods We performed an anonymous survey, mailed to 40, 000 donors in 2008, including questions about symptoms, height, weight, sex, and donation status. Reaction rates were compared to those recorded in our database. Possible risk factors were assessed for various reactions. Results The response rate was 45.5%. A total of 32% of first‐time and 14% of repeat donors reported having any adverse symptom, most frequently bruising (84.9 per 1000 donors) or feeling faint or weak (66.2 per 1000). Faint reactions were two to eight times higher than reported in our database, although direct comparison was difficult. Younger age, female sex, and first‐time donation status were risk factors for systemic and arm symptoms. In females, low estimated blood volume (EBV) was a risk factor for systemic symptoms. Only 51% of donors who consulted an outside physician also called Canadian Blood Services. A total of 10% of first‐time donors with reactions found adverse effects information inadequate. Conclusion This study allowed us to collect more information about adverse reactions, including minor symptoms and delayed reactions. Based on our findings of the risk factors and frequency of adverse reactions, we are implementing more stringent EBV criteria for younger donors and providing more detailed information to donors about possible adverse effects and their management.